The Effectiveness Of Fish Length Measurement System Using Non-Contact Measuring Approach - Jamaluddin, Muhammad Herman; Chong, Siong Seng; Shukor, Ahmad Zaki; Ali @ Ibrahim, Fariz; Miskon, Muhammad Fahmi; Mohd Aras, Mohd Shahrieel; Md Ghazaly, Mariam; Ranom, Rahifa (Penerbit UTM Press, 2015)
-